EFECTO DE LA ADICIÓN DE AGUACATE A LA ALIMENTACIÓN HABITUAL SOBRE LOS NIVELES DE LÍPIDOS EN PERSONAS CON DISLIPIDEMIA (Universitas Scientiarum, 2004)
The purpose of this study was to describe the effect of the daily  consumption of avocado, a good source of mono-unsaturated fatty acids, on serum lipid levels in dislipidemic subjects. The sample included thirty subjects between 30 and 65 years of age, who are treated by the Andes  Clinic in Tunja. Anthropometry, food frequency and a lipid profile were assessed. Individuals were required to consume 250 g of avocado daily for 4 weeks. Descriptive statistics and a t-test were used. All test  results were considered significant at p< 0.05. Weight gain during the 4-week experimental period for men was 2.7 kg and for women 2.3  (p